Differential impact of lifestyle factors on 2-hour glucose values in individuals with type 2 diabetes: potential for more personalized interventions - Hanno Pijl; Tim Snel; Tanja Krone; Regina J M Kamstra; Hannah M Eggink; Albert A de Graaf; Iris M de Hoogh (BMJ Open Diabetes Research & Care)
Introduction Lifestyle determinants of 2-hour glucose concentration in people with type 2 diabetes and interindividual differences need to be identified.Research design and methods 38 participants with type 2 diabetes, treated with lifestyle advice and/or metformin, tracked their physical activity, sleep and dietary intake, while continuously monitoring interstitial glucose concentrations for 11 periods of four consecutive days each. A linear mixed-effects model was used to quantify the effect of sleep, stress, current glucose, carbohydrate intake and exercise on glucose levels 2 hours later.Results The final model identified carbohydrate intake (grams) in the past 5 min as well as in the past 30 min, sleep duration during the previous night (hours) and physical activity (metabolic equivalents) over the past 12 hours as significant fixed effects that influenced glucose concentrations 2 hours later. In addition, carbohydrate intake in the past 5 and past 30 min, and physical activity in the past and future 30 min were included as random or individualized effects. Although carbohydrate intake led to increased glucose concentrations in 2 hours in all individuals, the magnitude of this effect varied between individuals. The physical activity on glucose concentrations in 2 hours varied among individuals as well, in terms of magnitude and in terms of direction (showing either increase or decline).Conclusions Carbohydrate intake, sleep and physical activity at specific points in time have both fixed as well as individualized effects on glucose concentrations 2 hours later in individuals with type 2 diabetes. Interindividual differences in glycemic response to lifestyle components call for personalized advice in the management of type 2 diabetes.